Reversal sprawl. Land-use regulation, society and institutions in Proseccotown. (December 2020) - Basso, Matteo; Vettoretto, Luciano
Highlights: a process of reversal sprawl has occurred in Proseccotown and is still ongoing. such process is influenced by institutional regulations, particularly national. reversal sprawl brings to massive land-use changes and social conflicts. ordinary local land-use plans are quite inertial compared to these transformations. Abstract: This paper discusses the reversal sprawl hypothesis, a phenomenon which occurs in globalized agro-industrial territories such as wine-growing areas. Here, it is no longer scattered or dispersed buildings that "colonize" and "threaten" agricultural areas, but the contrary. Empirical evidences derive from the case of the area where the Italian Prosecco sparkling wine is historically produced, which is very significant for its current success in international trade and the consequent massive spread of viticulture. Through quantitative and qualitative analyses, this paper presents the socio-economic and institutional origins of such a reversal sprawl, as well as its consequences in terms of land-use changes and regulation.